Decade of Despair: The Contested Rebuilding of the Nahr al-Bared Refugee Camp, Lebanon, 2007–2017 - Knudsen, Are John (Refuge, 2018)
In mid-2007 the Nahr al-Bared refugee camp near Tripoli was destroyed by the Lebanese Army battling an insurgent Islamist group, Fatah al-Islam. Displacing about 30,000 Palestinian refugees, it was one of the largest internal battles in post–civil war Lebanon. A decade later, the camp has yet to be fully rebuilt; indeed, reconstruction has been slow, confictual, and underfunded. Rebuilding the camp has been contested and delayed by political opposition, funding shortfalls, and complex ownership of land and property. About half of the displaced families have been able to return, the remainder are internally displaced, living temporarily in other camps or rented apartments. This article analyzes the slow-paced reconstruction of the Nahr al-Bared camp and especially what can be learnt from rehousing refugees in a militarized space of exception.